Analisis Kelimpahan Udang Putih di Estuaria Abudonek Kabupaten Malaka - Nahak, Konsulatriks Noviyanti; Atini, Blasius; Kolo, Sefrinus M. D. (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
Research with the title "Analysis of White Shrimp Abundance in the Abudenok Estuary of Malacca Regency". The purpose of this study was to determine the abundance of white shrimp in the Abudenok Malacca estuary and to find the parameters of the physical-chemical relationship to the abundance of white shrimp in the Abudenok estuary of Malacca Regency. The subject of this research is White Shrimp. The research data were obtained from the results of fishing catches using a 4 m diameter net. The study was conducted once a week for three weeks in the central and lower reaches of the Abudenok estuary. The results of the analysis of the abundance of white shrimp data shows the composition of the catch is different every week. In the first week the middle Estuary catches 158 white shrimp while the downstream Estuary captures fighting 234 tails In the second week the middle Estuary catches white shrimp winning 147 tails while the downstream Estuary catches white shrimp caught 356 tails. In the second week the middle Estuary catches 174 white shrimp while the downstream Estuary catches fighting 276 white shrimp. Effect of physical-chemical parameters on the abundance of 21.5 0C - 29 0C, current velocity of 0.13 ms-0.18 ms-1, salinity of 26.00 ppt - 29.00 ppt and sand substrate. The author concludes that the abundance of white shrimp in the Abudenok estuary is influenced by physical-chemical parameters, especially temperature, current speed and substrate.